Contrast‐induced encephalopathy following cardiac catheterization. Issue 2 (29th November 2016) - Spina, Roberto; Simon, Neil; Markus, Romesh; Muller, David WM; Kathir, Krishna
Abstract : Objectives: To describe the epidemiology, pathophysiology, clinical presentation, and management of contrast‐induced encephalopathy (CIE) following cardiac catheterization. Background: CIE is an acute, reversible neurological disturbance directly attributable to the intra‐arterial administration of iodinated contrast medium. Methods: The PubMed database was searched and all cases in the literature were retrieved and reviewed. Results: 52 reports of CIE following cardiac catheterization were found. Encephalopathy, motor and sensory disturbances, vision disturbance, opthalmoplegia, aphasia, and seizures have been reported. Transient cortical blindness is the most commonly reported neurological syndrome, occurring in approximately 50% of cases. The putative mechanism involves disruption of the blood brain barrier and direct neuronal injury. Contrast‐induced transient vasoconstriction has also been implicated. Symptoms typically appear within minutes to hours of contrast administration and resolve entirely within 24–48 hr. Risk factors may include hypertension, diabetes mellitus, renal impairment, the administration of large volumes of iodinated contrast, percutaneous coronary intervention or selective angiography of internal mammary grafts, and previous adverse reaction to iodinated contrast. Characteristic findings on cerebral imaging include cortical and sub‐cortical contrast enhancement on computed tomography (CT). Imaging findings in CIE may mimic subarachnoid hemorrhage or cerebral ischemia; the Hounsfield scale on CT and the apparent diffusion coefficient on magnetic resonance imaging (MRI) are useful imaging tools in distinguishing these entities. In some cases, brain imaging is normal. Prognosis is excellent with supportive management alone. CIE tends to recur, although re‐challenge with iodinated contrast without adverse effects has been documented. Conclusions: CIE is an important clinical entity to consider in the differential diagnosis of stroke following cardiac catheterization. Given that prognosis is excellent with supportive management only, physicians should be aware of it, and consider it prior to initiating thrombolysis. © 2016 Wiley Periodicals, Inc.